Engineering Synergy: Energy and Mass Transport in Hybrid Nanomaterials. (5th March 2015) - Cho, Eun Seon; Coates, Nelson E.; Forster, Jason D.; Ruminski, Anne M.; Russ, Boris; Sahu, Ayaskanta; Su, Norman C.; Yang, Fan; Urban, Jeffrey J.
<x xml:space="preserve">Abstract</x> An emerging class of materials that are hybrid in nature is propelling a technological revolution in energy, touching many fundamental aspects of energy‐generation, storage, and conservation. Hybrid materials combine classical inorganic and organic components to yield materials that manifest new functionalities unattainable in traditional composites or other related multicomponent materials, which have additive function only. This Research News article highlights the exciting materials design innovations that hybrid materials enable, with an eye toward energy‐relevant applications involving charge, heat, and mass transport.